Efficiency of Antibiotics in Children with Acute Respiratory Infection Complicated by Pneumonia Dependent on the Acetylation Type in the Far North Regions - A. V. Erbasskaya; V. V. Ivanova; L. V. Govorova; V. V. Belova; L. N. Bulovskaya (Антибиотики и Химиотерапия, 2020)
Clinical characteristics of some diseases are defined by the phenotype of metabolic reactions, for example N-acetylation. Genetic polymorphism due to the activity of N-acetyltransferase (N-AT) is common in the majority of human populations. Consequently, persons with «slow» or «fast» acetylation phenotype should be identified. N-AT catalyzes acetylation of a number of medical products. Efficiency of pharmacotherapy is mostly associated with the specific features of medical products biotransformation. The processes of biotransformation with participation of acetyltransferase, monooxygenase or other ferment systems are under the gene control. The aim of the study was to characterize the features of the clinical course of acute respiratory infection complicated by pneumonia as dependent on the acetylation phenotype to predict the character of the disease and optimize the used antibiotic therapy among the native population (Yakut) and the arrived (Russian) in the Far North Regions (Sakha, Yakutia). 112 children with acute respiratory infections complicated by pneumonia and 49 practically healthy ones were examined. For the children with low N-AT activity (less than 30%) it was recommended to be treated with gentamicin which directly takes part in the acetylation and provides the antibiotic therapy efficiency in 80% of the cases. The use of cephalosporin antibiotics (β-lactams), the metabolism of which is not directly connected with acetylation reactions provided the efficiency in 20% of the cases.